Optimalisasi Pembelajaran Bahasa Arab melalui Model Pembelajaran Komunikatif-Eklektik - Baiq Tuhfatul Unsi (Muróbbî: Jurnal Ilmu Pendidikan, 2017)
The learning method of Arabic language had been developed in line with developments in discipline of linguistics, psychology and research on teaching. This development is a logical consequence of differences in theoretical and empirical foundation. Every method has advantages and disadvantages, so there is no proper method completely. This anxiety show an eclectic method that combines the operational techniques of methods that are considered objectively and effectively by teachers. Learning method Communicative-Eclectic is communicative learning method performed by eclectic method. Eclectic method is built on the assumption that each method has its strengths and weaknesses, and that the implementation of a method certainly with a dealing objective conditions that do not allow the implementation of the method as a whole. Implementation of this eclectic-communicative method, example, by applying three types of drill, the drill mechanical-manipulative with drill communicative, and semi-communicative drill. The teaching process more emphasis on finesse speak, write, read and understand specific meanings. By this method students can be given training example; practice conversing in a foreign language that can be done by an individual or group between students or teachers and students. So that teaching and learning will be very varied and not focused on one activity.